Pengaruh Kepribadian dan Komitmen Organisasional Terhadap Organizational Citizenship Behavior pada Pegawai Kantor Satuan Polisi Pamong Praja Kabupaten Kubu Raya - Gunawan, Indra B1021161034 (Jurnal Manajemen Update, 2020)
ABSTRACTThis study aims to determine the effect of Personality and Organizational Commitment on Organizational Citizenship Behavior in the Civil Service Police Unit in Kubu Raya Regency. The population in this study were all Civil Service Police Employees in Kubu Raya Regency with 35 people. The sample taken in this study used a saturated sampling technique of 35 people. The data analysis method of this study uses multiple regression analysis. Based on the results of the study Personality variables have a significant effect on Organizational Citizenship Behavior and Organizational Commitment variable has a significant effect on Organizational Citizenship Behavior. Keywords: Personality, Organizational Commitment, Organizational Citizenship Behavior ReferensiAdolf, Heuken SJ, et al. 1979. Pedoman untuk Mengenal Diri, Tantangan Kepribadian, Jilid I & II. Cet. Ke-3. Yogyakarta: Kanisius.Aldag, R. & Reschke, W. 2015. Employee value added: Measuring Discretionary Effort and its Value to the Organization. Center for Organization Effectiveness.Allen, N.J. & J.P. Meyer. 2010. The Measurement and Antecedents of Affective, Continuance and Normative Commitment to the Organizational. Journal of Occupational Psychology. 63 (!). 1-18.Andre, Rae. 2008. Organizational Behavior, An Introduction to Your Life in Organizations. New Jersey: Person PrenticeAnshori, M. Isa. 2013. Relasi Komitment Organisasi dan Kepuasan Kerja terhadap Organizational Citizenship Behavior (OCB) (Studi Kasus di Poltekes Surabaya. 42-50Anwar, Suroyo. 2009. Pemahaman Individu, Observasi, Checklist, Interview, Kuesioner, dan Sosiometri. Yogyakarta: Pustaka Pelajar.Ariani, Dorothea Wahyu. 2014. Relationship Personality, Job Satisfaction, Organizational Commitment and Organizational Citizenship Behavior of Service Industries in Indonesia. Res.J. Business Manage, 8 (3), 262-283.Arikunto, S. 2010. Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta: Rineka Cipta.Dessler, G. 2000. Human Resource Management, 8th  edition. New Jersey: Prentice-Hall,IncFurnhman, A. 2002. The Psychology of Behavior at Work, The Individual in The Organization. Hove and New York : Psychology Press. Gajah Mada University Press.Ghozali, Imam. 2016. Aplikasi Analisis Multivariete Dengan Program IBM SPSS 23 (Edisi 8). Catatan ke VIII. Semarang: Badan Penerbit Universitas Diponergoro.Greenberg, J. & Robert A. Baron. 2003. Behavior in Organization International Edition. New Jersey: Prentince Hall.Hariandja, Marihot T.E. 2002. Manajemen Sumber Daya Manusia. Jakarta: Grasindo.Iskandar. 2009. Metodologi Penelitian Kualitatif. Jakarta: Gaung Persada Press.Ivancevich, et al. 2007. Perilaku dan Manajemen Organisasi Jilid 1 Edisi Ketujuh. Jakarta: ElanggaKarlinger. 2006. Asas-Asas Penelitian Behavioral. Edisi Ketiga. Yogyakarta: Gadjah Mada University Press.Kartono, K., & Gulo. 2006. Kamus Psikologi. Bandung: CV. Pionir Jaya.Kasiram, Moh. 2008. Metodologi Penelitian. Malang: UIN-Malang Pers.Kinicki, et al. 2012. Organizational Behavior: Key Concept, Skill and Best Pratices. New York: McGraw-HillKoswara, E. 2005. Teori-Teori Kepribadian Edisi II. Bandung: PT. ErescoKusumawardhani, P.S. 2010. Hubungan Komitmen terhadap Organisasi dengan Organizational Citizenship Behavior pada Pegawai Negeri Sipil di Biro Organisasi dan Kepegawaian Setda Provinsi Jawa Tengah. Skripsi. Semarang: Universitas Katolik Soegijapranata.Lamidi. 2008. Pengaruh Kepemimpinan Transformasional terhadap Organizational Citizenship Behavior dengan Variabel Intervening Komitmen Organisasional. Jurnal Ekonomi dan Kewirausahaan. Vol. 8 No.1, 25-37Luthans, Fred. 2012. Perilaku Organisasi. Yogyakarta: Andi.McShane & Glinow. 2008. Organizational Behavior. New York: McGraw-Hill.Morrison, E.W. 1994. Role Definition and Organizational Citizenship Behavior: The Importance of The Employee’s Perpective. Academy of Management Journal. 37, 1543-1567.Nasution. 2006. Budaya Organisasi,Kepuasan Kerja, Komitmen Organisasional dan Keinginan Berpindah: Investigasi Empiris Pada Berbagai Unit Kerja di Universitas Bengkulu. Bengkulu: Universitas Bengkulu.Nawawi. Hadari. 2001. Manajemen Sumber Daya Manusia untuk Bisnis yang Kompetitif. Yogyakarta: UGM.Nugraha, S.P.I, & Adnyani. 2018. Pengaruh Budaya Organisasi, Komitmen Organisasi, dan Kopetensi Terhadap Organizational Citizenship Behavior Pada Setda Kota Denpasar. Jurnal Manajemen Unud, 7(1), 1-28.Nurgiyantoro, Burhan. 2012. Statistika Terapan untuk Penelitian-Penelitian Ilmu Sosial. Yogyakarta: Gadjah Mada University Press.Omer, Frank Unal. 2013. Relationship Between The Facets of Job Satisfaction and The Dimensions of Organizational Citizenship Behavior: Mediating Role of Organizational Commitment. Suleyman. Demirel University The Journal of  Faculty of Economics and Administrative Sciences Y., 18(1), 234-269.Organ, et al. 2006. Organizational Citizenship Behavior: Its Nature, Antecedents, and Consequences. California: Sage Publication.Pangastuti. 2018. Pengaruh Dimensi Kepribadian The Big Five Personality Terhadao Organizational Citizenship Behavior. Jurnal Ekonomi Universitas Kadiri. 3(1), 87-103.Prasetio, . 2015. The Effects of Job Satisfaction and Organizational Commitment on Organizational Citizenship Behavior. Jurnal Siasat Bisnis. 19(2), 99-108.Purba, Eflina .D, & Ali, N.L.S. 2004. Pengaruh Kepribadian dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior. Makara, Sosial Humaniora. 8(3). 105-111.Raharjo, Sugeng. 2016. Pengaruh Motivasi dan Kepribadian Terhadap Organizational Citizenship Behavior Guru SMA Pada SMA NEGERI 1 TENGGARONG. JEMI. 16(2).Rakhmat, Jalaluddin. 1996. Psikologi Komunikasi. Bandung: Remaja RosdakaryaRini, Setya, G. & Raharjo. 2014. Analisis Pengaruh Komitmen Organisasional Terhadap Organization Citizenship Behavior. Diponegoro Journal of Management. 1-15.Rivai. 2003. Manajemen Sumber Daya Manusia untuk Perusahaan: Dari Teori Ke Pratik. Jakarta: PT. Rajagrafindo Persada.Robbins, S.P. 2015. Perilaku Organisasi, Edisi 12. Jakarta: PT. PrenhalindoRobbins, S.P & Timothy A. Judge. 2015. Perilaku Organisasi, Edisi 16. Jakarta: Salemba Empat.Saedy & Rastgar. 2015. Study of the Role of Personality Factors in Organizational Citizenship Behaviors. Trends Journal of Sciences Research. 2(2), 50-55.Sahertian, P. 2011. Improving Employee’s Organizational Commitment, Self-Efficacy, and Organizational Citizenship Behavior Through the Implementation of Task-Oriented and Relationship-Oriented Leadership Behavior. The Business Review, 17(2),48-60.Sambung, Roby. 2014. Pengaruh Kepribadian Terhadap Organizational Citizenship Behavior dengan Komitmen Organisasional sebagai Intervening. Jurnal Manajemen dan Akuntansi, 3(1).Sani. 2013. Role of Procedural Justice, Organizational Commitment and Job Satisfaction on Job Performance: The Mediating Effects of Organizational Citizenship Behavior. International Journal of Business and Management, 8(15).Sekaran, Uma. 2011. Research Methods for Business. Edisi I dan II. Jakarta: Salemba Empat.Sukmadinata. 2003. Landasan Psikologi Proses Pendidikan. Bandung: Remaja Rosdakarya.Sugiyono. 2016. Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Suryani, et al. 2019. The Effect of Organizational Compensation and Commitment to  Organizational Citizenship Behavior in the Cooperative and Small, Middle Enterprises Department of Bali Province. International Journal of Contemporary Research and Review, 10(1)Titisari, Purnami. 2014. Peranan Organizational Citizenship Behavior (OCB) Dalam Meningkatkan Kinerja Karyawan. Mitra Wacana Media: JakartaWahyuni, et al. (2017). Pengaruh Kepribadian dan Komitmen Organisasi Terhadap   Organizational Citizenship Behavior (OCB) Pada Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman. Journal Administrative Reform, 5(1).Widiyanto, Joko. 2010. SPSS for Windows Untuk Analisis Data Statistik dan Penelitian. Surakarta: BP-FKIP UMS.